Long-term Care Management Guidelines for Dependent Elders in a Muslim Community, Southern Thailand - เจริญวงศ์ สรวงสุดา; พรทิวา พรทิวา; จันทร์แสงรัตน์ นิภารัตน์; สีหวาน เพียงตะวัน; นิรมาณกุล รติ (Princess of Naradhiwas University Journal, 2018)
This qualitative research was to propose guidelines for developing a long-term care management for dependent elderly within a Muslim community in southern Thailand. The sample group consisted of 37 people, including 5 dependent elders, 5 caregivers and 27 community stakeholders. Data collection includedobservation, in-depth interview, focus group and field note, together with community meeting and brainstorming. Content analyses were done for qualitative data. The findings revealed that the associated community lacked care management for the elderly corresponding to Muslim culture context. In addition, empirical integration in the associated community for long-term care management for the dependent elderly was absent. Thus, guidelines for long-term care management in dependent elderly composed of 1) associated community establishing health care volunteers to provide home visits, 2) home visit activities for the dependent elderly within the Muslim culture and 3) support from health partnerships in promoting the potential of care management for elders. The Guidelines are long-term care management for the dependent elderly through the integration of the community, public consciousness and Muslim culture.